1985
DOI: 10.2172/5875386
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic noise associated with the MOD-1 wind turbine: its source, impact, and control

Abstract: This report summarizes extensive research by staff of the Solar Energy Research Institute and its subcontractors conducted to establish the or1g1n and possible amelioration of acoustic disturbances associated with the operation of the DOE/NASA MOD-1 wind turbine installed near Boone, North Carolina.Results have shown that the most probable source of this acoustic annoyance was the transient, 'unsteady aerodynamic lift imparted to the turbine blades as they passed through the lee wakes of the large, cylindrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 6 publications
6
15
0
Order By: Relevance
“…According to Cooper, two residents were clearly more sensitive than the other four; the sensations experienced by the residents seemed to be more related to a reaction to the operation of the wind turbines than to the sound or vibration of the wind turbines. This echoes earlier findings from Kelley [121] who investigated complaints, from two residences, that were thought to be associated with strong low-frequency sound pulses from the experimental downwind MOD-1 wind turbine. The low-frequency sound pulses were generated when a turbine blade passed the wind wake behind the mast.…”
Section: Effect Of Vibrationssupporting
confidence: 88%
“…According to Cooper, two residents were clearly more sensitive than the other four; the sensations experienced by the residents seemed to be more related to a reaction to the operation of the wind turbines than to the sound or vibration of the wind turbines. This echoes earlier findings from Kelley [121] who investigated complaints, from two residences, that were thought to be associated with strong low-frequency sound pulses from the experimental downwind MOD-1 wind turbine. The low-frequency sound pulses were generated when a turbine blade passed the wind wake behind the mast.…”
Section: Effect Of Vibrationssupporting
confidence: 88%
“…This figure is very close to that found by Kelley [64] and his colleagues cited above, although the true figure may well be higher. The authors observed that epidemiological research on low frequency noise is scarce and suffers from methodological shortcomings.…”
Section: Public Health's Responsibilitiessupporting
confidence: 90%
“…If Public Health doctors actually visited the families who have been forced to abandon their homes they might demand to see the necessary studies conducted. They would learn that some of the worst affected are small children who are very often put in the smaller bedrooms which are worst impacted by noise [64]. There is also the intriguing possibility that if Infrasound is conducted through the skin [54], young children will receive a larger dose because their surface area is greater in relation to their volume in comparison to adults.…”
Section: Public Health's Responsibilitiesmentioning
confidence: 99%
“…If the presence of the tower is important for noise generation, then research may be needed to investigate possible modifications to the tower construction, such as changing the tower from a solid cylinder to a structure that is much less effective in allowing the air between the blade and tower to be compressed as the blade passes (for example, a lattice-type tower used for high voltage power lines [31]). Lattice towers were used to support the downwind turbines of the 1980s [1], and the interaction of the turbine blades with the flow disruption caused by the support legs was considered to be responsible for the thumping noise that residents complained of. However, for upwind turbines, there is no wake problem but there exists a wind velocity deficit in the vicinity of the support tower that leads to the generation of impulsive aerodynamic noise as discussed above.…”
Section: Mechanisms and Control Of Wind Turbine Noise Generationmentioning
confidence: 99%
“…The location of the tower upwind of the rotor resulted in very turbulent flow being incident on the turbine blades which, in turn, resulted in the generation of thumping sounds as the blades passed close to a leg of the tower that generated the flow disturbance. The thumping noise disturbed nearby residents and caused cause rattling of dishes and annoyance for a number of residents living within 3 km of a single turbine [1]. Some residents reported feeling the sound more than hearing it, which resulted in a sensation of uneasiness and personal disturbance.…”
Section: Introductionmentioning
confidence: 99%